Moraceae endémicas del Perú - Cáceres, Pamela (2006)
The Moraceae are represented in Peru by 19 genera and 128 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly trees and hemiepiphytes. Here we recognize two endemic species, in the same number of genera. These endemic species are found in Humid Lowland Amazonian Forests region, between 115 and 220 m elevation. Both endemic Moraceae have been recorded in within Peru’s protected areas system.